2012
DOI: 10.1155/2012/636045
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Reviewing the Accuracy and Reliability of a Five-Level Triage Process (Canadian Triage and Acuity Scale) in a Community Emergency Department Setting: Building the Crowding Measurement Infrastructure

Abstract: Objectives. Triage data are widely used to evaluate patient flow, disease severity, and emergency department (ED) workload, factors used in ED crowding evaluation and management. We defined an indicator-based methodology that can be easily used to review the accuracy of Canadian Triage and Acuity Scale (CTAS) performance. Methods. A trained nurse reviewer (NR) retrospectively triaged two separate month's ED charts relative to a set of clinical indicators based on CTAS Chief Complaints. Interobserver reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[38,39] There are different studies about the accuracy, reliability and validity of 5-level triage systems for the acute patient triage. [21,[32][33][34][35][36][37] In an observational study including 486 patients by Worster et al, [36] there was no statistical difference between ESI and CTAS triage systems. In a study including 900 patients conducted by eight educated triage nurses, in which Storm-Versloot et al [33] used MTS and ESI without using a triage algorithm, it was reported that ESI had a lower triage score than MTS (11% to 20%).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[38,39] There are different studies about the accuracy, reliability and validity of 5-level triage systems for the acute patient triage. [21,[32][33][34][35][36][37] In an observational study including 486 patients by Worster et al, [36] there was no statistical difference between ESI and CTAS triage systems. In a study including 900 patients conducted by eight educated triage nurses, in which Storm-Versloot et al [33] used MTS and ESI without using a triage algorithm, it was reported that ESI had a lower triage score than MTS (11% to 20%).…”
Section: Discussionmentioning
confidence: 95%
“…[20] It was also shown that the triage level application has changed according to the number of incoming patients; while 5-level ESI triage system applied in 78.3% of crowded emergency departments having more than 100.000 or more annual urgent patients, 3-level triage system has been applied in 60.2% of the emergency departments having less than 1.000 annual urgent patients. [20,21] As suggested in the statement published in 2009 by the Ministry of Health of Turkish Government, the 3-level triage system has been commonly used in Turkey. In 3-level triage system, patients are categorized as emergent (red), urgent (yellow) and non-urgent (green).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also notable limitations to the standardization of triage. Multiple studies demonstrate that the CTAS system has low inter‐rater agreement, with nurses inconsistently categorizing patients (Dallaire, Poitras, Aubin, Lavoie, & Moore, ; Howlett & Atkinson, ). Notably, in many of the research studies conducted on CTAS inter‐rater agreement and reliability, disagreement is inherently assumed to be undesirable (Dallaire et al., ; Fernandes et al., ); differing interpretations of acuity represents a breach of standardization in which a triage nurses’ personal subjectivities or inadequate education or experience result in inappropriate decision‐making (Dallaire et al., ).…”
Section: Exemplars: Standardization In Nursing Practicementioning
confidence: 99%